A Measure of Impact of Electronic Human Resource Management (e-HRM) On Organization Performance: The Mediating Effects Of Competitive Advantage: An Exploratory Factor Analysis - Alhadban, Rami; Awang, Zainudin; Afthanorhan, Asyraf (International Journal of Psychosocial Rehabilitation, 2020)
This study talks about the relationship of organization performance and electronic human resources management. The subject of organization performance a common theme in literature where there are many pieces of research that based on their various analyzes offers a range of assertions (Aleali & Qasim, 2011). Make an analysis of Exploratory factors (EFA) is for tool validation used in this research it is one of the objectives of the research. The questionnaire was taken the user in this study of the eight studies, namely: Al-Awadh, M. A. (1996), Saleh, M. M. (2014). Al.Hmouze, L.H. (2016), Atallah, A. A. (2016), Bharti, P. (2015). Al Shobaki, M. J. et al (2017), and Stone, D. L., et a l (2015), and Quansah, N. (2013). It consists of three constructs and five-component 100 questionnaires collected after distributed, construct separately EFA was done for each. The results show that all of the three constructs have three component or dimension, The factor loading for every item in each construct is> 0.6, The Kaiser-Meyer-Olkin values were above the recommended threshold of 0.6 (Kaiser, 1974) and Bartlett's Test of Sphericity reached statistical significance indicating the correlations were sufficiently large for exploratory factor analysis. All the Cronbach's alpha values were above the threshold value of 0.70, this means the items All are reliable in this study. The found a valid and reliable instrument for measuring in this study for the activity of organizational performance components in the e-HRM. ,